A Comprehensive Evaluation of the Role of Social Workers in Reducing Burnout among Nursing Technicians in High-Stress Hospital Environments - ALHARBI, HAMDAH MOHAMMED; ALROILEY, WANSAH SOUDI; ALMUTAIRI, LINA SAEED MUFAKKIR; ALRAWILIY, AREEJ SOODI; ALDQMANI, HANA HAIL ABDULRAHMAN; ALRWILI, ARWA MUHAMMED; ALENZI, NOORA SALEH; AL-OTAIBI, MANAL NAZAL; ALOTAIBI, OHUD HAMOUD ABDULLAH; ALONAZI, KHOLOU HOMUD (Journal of Ecohumanism, 2024)
Nursing technicians are a vulnerable population that experiences burnout due to working in context of high stress hospitals and this phenomenon reduces the health of the nurses and the quality of care afforded to the patients. Based on their knowledge and practice backgrounds in mental health, crisis, as well as, coping interventions, social workers are well-suited for addressing this problem. In this paper a performance assessment of social workers is conducted, based on a study of strategies and interventions averted to decrease burn out among nursing technicians in a hospital sector. Employing both the qualitative and quantitative approaches, this study evaluates the results of the studies performed to reduce the burnout level and provides the qualitative information of the strategies that the social workers should use to assist the nursing technician under great pressure. This research shows that social workers are strategic in offering support, helping clients work through stress, and fighting for systems that reduce stress. However, the research also outlines some difficulties for integrating social work with clinical teams in the future.